Energy Saving Using Green Computing Approach for Internet of Thing (IoT) Based Tiny Level Computational Devices - Ooruchintala, Obulesu; Munisekhar, Mahendra; Kallam, Suresh; Madda, Rajasekharababu (Recent Advances in Computer Science and Communications, 2020)
Background: It is important to minimize energy consumption that improves battery life, system reliability and other environmental concerns and energy optimization is turning into a very important in the tiny devices in Internet of Things (IoT) research area with the increasing demand for battery operated devices. IoT need battery life improvement in tiny device, so power optimization is significant. Methods: In this paper an Experimental Design (ED) is proposed for the performance improvement in terms of energy and run time. Among the many sutras of optimizations, by using the Green computing the products are work with limited battery. This proposed technique results in reduce power conumption. Results: The result shows that the proposed Energy saving on tiny devices based on IoT are the energy consumed and run time by the code after applying optimization techniques, which is the minimum among all four. Besides reduction in energy and runtime, reduction in the number of executed instructions is also achieved. Conclusion: This paper comprehensively describes the. Its average performance percentage reached 91.1 % for energy, the performance reduction in energy and runtime, reduction in the number of executed instructions is also achieved. The performance holds better for Common subexpression elimination. So, we can say the proposed Experimental Design (ED) is effective in reduction of energy consumption and runtime of the program.
Keywords: experimental design